The First Christmas - Campbell, Rod (Macmillan Publishers Limited, 2011)
This simple, warm retelling of the Christmas story has easy-to-follow sentences and bright, appealing artwork, making it perfect for young children. Sure to become a family favourite, shared and loved at Christmas time year after year.
Keywords: Christmas & Advent; Holidays & Celebrations; Juvenile Fiction